Pemanfaatan Tailing Bauksit sebagai Bahan Campuran Pengganti Pasir pada Pembuatan Paving Block - Maya Santi; Syarifah Aqla (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Politeknik Pratama Mulia Surakarta, 2018)
Bauxite tailing is a by product of bauxite washing. The amount of waste from the bauxite tailings can reach about 50% of the dry weight of the bauxite before washed. The increasing demand for bauxite causes the amount of exhaust produced to be even greater. This risks causing environmental pollution problems requiring an alternative treatment and one of the solutions is utilize the bauxite tailings as a mixture of sand substitutes in the manufacture of paving blocks. The role of sand is replaced by a 50% increase in market price so that in this study a compressive strength test will be conducted on the strength of paving blocks with sand mixture (as sold in the market) with paving blocks with bauxite tailings mixed then comparison. This utilization is to minimize the environmental impacts, to reduce the accumulation of materials at the washing site, and in the future can be increasing value products that become business opportunities for affected communities due to bauxite mining. Based on the research, there is a found the average value of uniaxial compressive strength of sampel 50% : 50% is 17.19 Mpa. That is smaller than the value of uniaxial compressive strength of sampel 60% : 40%, 17.62 MPa. The meaning of compressive strength value of the sample is 60%: 40% more optimal than the sample with the ratio 50%: 50% because the value of compressive strength is included in SNI-03-0691-1996 ie on the quality of B.